Partisipasi Masyarakat Dalam Penanganan Stunting Melalui Nagari Pintar Di Nagari Ganggo Hilia Kabupaten Pasaman - Hs, Putri Hidayah; Yoserizal, Yoserizal; Putera, Roni Ekha (Department of Sociology, Faculty of Social and Political Science, Universitas Padjadjaran, 2023)
This research is motivated by the high prevalence of stunting in one of the Pasaman districts, especially Nagari Ganggo Hilia. In this Nagari, a program called “Smart Nagari” that designed as the pilot for handling stunting. this study aims to uncover how the Ganggo Hilia community engages regarding stunting through Nagari Pintar. The descriptive qualitative approach is needed to collect and analyze data. Primary data that gathered over in-depth interviews and direct observation at the research location. The theory used is the stages of community participation in handling stunting in Nagari Ganggo Hilia is already active but not optimal. The community has felt the benefits of activities at the integrated healthcare center. However, regarding the results, there hasn’t been a significant reduction in the stunting rate, yet the community has actively participated in activities at the integrated healthcare center. For indicators of decision making, implementation, and evaluation, society has already engaged. So that in this case, the government can provide programs that can be collaborated with the Smart program itself to reduce stunting rates.